2012
DOI: 10.1080/01449290903121360
|View full text |Cite
|
Sign up to set email alerts
|

Marketing implications of traditional and ICT-mediated leisure activities

Abstract: This study investigates the role of traditional and information and communication technology (ICT)-mediated leisure activities in consumer behaviour. An online survey of 558 members and 1,319 ex-members of an Australian DVD rental company gathered preferences for nine traditional leisure activities and seven ICT-mediated leisure activities. The results of a cluster analysis showed four clusters with significant cluster differences across leisure activities as well as across demographics and consumer behaviours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The occupation of the head of household affects travel intention and level of expenditure. These results match the data from Zorn et al (2012). To summarize the above findings, with respect to social status, the education level and occupational classification should be used as a reference for marketing segmentation when planning tourism products.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The occupation of the head of household affects travel intention and level of expenditure. These results match the data from Zorn et al (2012). To summarize the above findings, with respect to social status, the education level and occupational classification should be used as a reference for marketing segmentation when planning tourism products.…”
Section: Resultssupporting
confidence: 79%
“…Therefore, higher education levels also increase travel expenditure. Zorn et al (2012) found that the demographic variables leisure activities and consumer behaviour were significantly different from each other. In other words, participation in leisure activities will be affected by individual and family behaviours, characteristics and occupations.…”
Section: Financial Factors Dsp1mentioning
confidence: 81%
“…Another difficulty for companies implementing churn models is that a firm's customers can be highly heterogeneous (Bell et al , 2002; Lewis, 2006), and, therefore, different churn models are required for different segments of the firm's customers. Demographics are easily measured, but tend to be poor tools for predicting membership in different PB segments; firms require insights into how each individual customer thinks and feels about their products (Sivadis et al , 1998; Zorn and Murphy, 2007). These differences in preferences usually relate to situation‐specific variables, such as each customer's level of commitment to the relationship, their satisfaction with the firm's products, and their perceptions of the firm's quality and trustworthiness.…”
Section: Introductionmentioning
confidence: 99%